Real-time face recognition for human tracking system - Nawawi, Sophan Wahyudi; Mohd Zaini, Muhammad Zharif; Abdul Manaf, Mohamad Shukri; Ahmad, Nasarudin (Penerbit UTHM, 2020)
Computer-based human face detection and recognition systems proliferate in various sectors such as universities, factories and other organisation [1]. This system refers to a branch of computer technology that can recognise human faces in digital images...